2022
DOI: 10.15420/cfr.2021.34
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Therapy in Older Patients with Heart Failure with Reduced Ejection Fraction

Abstract: Older patients are becoming prevalent among people with heart failure (HF) as the overall population ages. However, older patients are largely under-represented, or even excluded, from randomised controlled trials on HF with reduced ejection fraction, limiting the generalisability of trial results in the real world and leading to weaker evidence supporting the use and titration of guideline-directed medical therapy (GDMT) in older patients with HF with reduced ejection fraction. This, in combination with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
(67 reference statements)
0
10
0
1
Order By: Relevance
“…Obese patients were also more likely followed up in nurse‐led HF clinics, which, as reported in another analysis from SwedeHF, are linked with more optimized use of pharmacological treatments 14 . Higher referral to nurse‐led HF clinics in obese patients might be at least partially explained by the younger age and higher comorbidity burden, with younger age having been perceived as a reason per se for better treatment by physicians, which might be linked to perceived reduced tolerance and limited evidence from RCT in older populations 15–17 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Obese patients were also more likely followed up in nurse‐led HF clinics, which, as reported in another analysis from SwedeHF, are linked with more optimized use of pharmacological treatments 14 . Higher referral to nurse‐led HF clinics in obese patients might be at least partially explained by the younger age and higher comorbidity burden, with younger age having been perceived as a reason per se for better treatment by physicians, which might be linked to perceived reduced tolerance and limited evidence from RCT in older populations 15–17 …”
Section: Discussionmentioning
confidence: 93%
“…14 Higher referral to nurse-led HF clinics in obese patients might be at least partially explained by the younger age and higher comorbidity burden, with younger age having been perceived as a reason per se for better treatment by physicians, which might be linked to perceived reduced tolerance and limited evidence from RCT in older populations. [15][16][17] An important finding was that obesity per se was associated with better and more intensive pharmacological treatment after extensive adjustments for all known and measured confounders, including variables linked with tolerance, that is blood pressure, renal function, heart rate, potassium levels, age, and also follow-up care. This suggests that in a proportion of non-obese patients GDMT might be inappropriately not initiated/up-titrated due to a perceived rather than actual limited tolerance to treatments or due to clinical inertia.…”
Section: Differences In Hfref Treatments and Patient Characteristics ...mentioning
confidence: 99%
“…Even though older persons have been underrepresented in RCTs [53][54][55], the favorable effect of disease-modifying medication among them has already been proven [56][57][58][59]. However, it is well known that in everyday clinical practice the initiation and optimization of GDMT in the aging population lags behind that of younger people.…”
Section: Predictive Factors Of the Discharge Application Of Triple Th...mentioning
confidence: 99%
“…The advent of new drugs able to positively influence the volume homeostasis in patients with heart failure (HF), such as sodium-glucose co-transporter 2 (SGLT-2) inhibitors and angiotensin receptor neprilysin inhibitors (ARNIs), opens the possibility of re-evaluating the long-term diuretic approach of HF in the outpatient setting and primary care. Recent studies have suggested several schemes for HF medication sequential introduction [ 1 , 2 ]. However, although loop diuretics (LDs) are one of the most commonly prescribed drugs in HF patients, there has yet to be a shared consensus regarding the time and the modality of dose reduction or withdrawal in stable HF.…”
Section: Introductionmentioning
confidence: 99%